ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI BAWANG MERAH LOKAL PALU DI DESA OLOBOJU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Pamusu, Sherley Siseraf; Alam, Max Nur; H., Sulaeman (AGROTEKBIS, 2013)
This study aims to determine the affect of land area, seed, fertiliser and labor to the local Palu onion production in the village Oloboju Biromaru Sigi Sub District Sigi District andthe incomes of local Palu onion farming at village Oloboju Sub Biromaru Sigi District Sigi. Respondents used in this study were 30 respondents or 13.82 % of the 217 households that farming oflocal Palu onion by using simple random sampling. The analysis showed that the simultaneously land area factor (X1), seeds (X2), fertilizer (X3) and labor (X4) very significant effect on farm production local Palu onion farming, with an F-count > F- table ( 299.354 > 2.76 ) at the Î± level of 5 % signicancy. The test results show that the t-test was highly significant on land area with t-> t -table (8.098 > 2.756), the seed was highly significant withÂ t-count > t-table (5.869 > 2.756), fertilizer was highly significant with t-count > t -table (3.978 > 2.756) and a significant on labor with t –count > t -table (2.836 > 2.756), respectively at the 1 % level Î±. The revenue analysis results showed that the average income of the respondent of Local Palu onion farmers Oloboju village in single growing season was Rp 59.913.000/ 0,67 ha or Rp89.511.454/ha.